Eliminating Categorical Exclusion Criteria in Crisis Standards of Care Frameworks. Issue 7 (2nd July 2020) - Auriemma, Catherine L.; Molinero, Ashli M.; Houtrow, Amy J.; Persad, Govind; White, Douglas B.; Halpern, Scott D.
Abstract: During public health crises including the COVID-19 pandemic, resource scarcity and contagion risks may require health systems to shift—to some degree—from a usual clinical ethic, focused on the well-being of individual patients, to a public health ethic, focused on population health. Many triage policies exist that fall under the legal protections afforded by "crisis standards of care, " but they have key differences. We critically appraise one of the most fundamental differences among policies, namely the use of criteria to categorically exclude certain patients from eligibility for otherwise standard medical services. We examine these categorical exclusion criteria from ethical, legal, disability, and implementation perspectives. Focusing our analysis on the most common type of exclusion criteria, which are disease-specific, we conclude that optimal policies for critical care resource allocation and the use of cardiopulmonary resuscitation (CPR) should not use categorical exclusions. We argue that the avoidance of categorical exclusions is often practically feasible, consistent with public health norms, and mitigates discrimination against persons with disabilities.